An evaluation on the dividend signalling theory in Singapore stock market - Koh, Nigel Jia Yuan (Nanyang Technological University, 2021)
Dividend signalling theory is one of the most debated theories in finance literature. This paper seeks to evaluate the dividend signalling theory in the Singapore Exchange (SGX), which is Asia’s most internationalised exchange. The data obtained includes dividend announcement events and financial data of the listed companies. The specification of the model by Nissim and Ziv is adopted while assuming a linear relation between future earnings and past earnings levels and changes. However, with empirical evidence suggesting the relationship to be highly nonlinear, this paper also adopted the specification of the model by Fama and French. The results provide weak evidence for the dividend signalling theory to hold in SGX. This could be explained by the strong accounting conservatism principle and lesser asymmetric information between shareholders and listed companies in SGX.